And yet they glow: thiazole based push–pull fluorophores containing nitro groups and the influence of regioisomerism. (18th June 2015) - Habenicht, Stefanie H; Siegmann, Michael; Kupfer, Stephan; Kübel, Joachim; Weiß, Dieter; Cherek, Doreen; Möller, Uwe; Dietzek, Benjamin; Gräfe, Stefanie; Beckert, Rainer
Abstract: Reported is a study on the influence of regioisomerism on the photophysical properties in 4-hydroxy-1, 3-thiazole-based push–pull-chromophores/fluorophores to evaluate the molecular structure–property relationship as a basic foundation for future design strategies concerning this class of dyes. Surprisingly, the nitro groups used as acceptors do not act as a fluorescence quencher, instead the derivatives synthesized exhibit quantum yields of 37–40%. Two 4-ethoxy-1, 3-thiazole derivatives which differ only in the positioning of their electron donating (methoxy) and electron withdrawing (nitro) groups have been synthesized and examined in terms of their photophysical properties, i.e. UV/Vis absorption and fluorescence emission spectra. Additionally, quantum chemical calculations have been performed to unravel the underlying fundamental transitions and to explain the experimental results.